(untitled) (Texas Journal of Medical Science, 2024)
This article defins chlamydial pneumonia, this disease, a subtype of atypical pneumonia, poses a significant health concern, particularly among pediatric populations. This retrospective study aims to investigate the clinical characteristics and treatment outcomes of chlamydial pneumonia in children aged 3 to 8 years. A total of 26 children with confirmed Chlamydia pneumoniae infection were examined, revealing notable respiratory and extrapulmonary manifestations. Clinical presentation varied, with symptoms ranging from rhinitis and tracheobronchitis to unproductive cough, fever, and chest pain. Bronchoobstructive syndrome was prevalent, accompanied by leukocytosis, eosinophilia, and accelerated erythrocyte sedimentation rate (ESR). Radiographic findings predominantly showed interstitial changes and increased vascular components. Macrolides emerged as the primary therapeutic agents, leading to clinical recovery within 10-14 days. These findings underscore the importance of early recognition and appropriate management of chlamydial pneumonia in pediatric patients.